On classes of ζ-uniformly q-analogue of analytic functions with some subordination results - Sarem H. Hadi; Maslina Darus; Badriah Alamri; Şahsene Altınkaya; Abdullah Alatawi (Applied Mathematics in Science and Engineering, 2024)
This article presents new classes of ζ-uniformly q-starlike and q-convex analytic functions of order υ using the principle of q-calculus. The renowned classes of starlike and convex functions are utilized to establish these classes. The investigation of these uniformly classes leads to the study of some geometric notions, including coefficient estimates, sharpness, distortion and growth theorems, and convex linear combinations. Furthermore, some subordination properties involving integral means inequalities and subordinate sequences are examined.